Corrosion of Borosilicate Glasses Subjected to Aggressive Test Conditions: Structural Investigations. Issue 10 (10th June 2016) - Thorat, Vidya S.; Mishra, Raman K.; Kumaran, Sudarsan V.; Kumar, Amar; Vatsa, Rajesh K.; Kaushik, Chetan P.; Tyagi, Avesh K.
Abstract : Sodium borosilicate (NBS) and barium sodium borosilicate (BBS) glasses, used for immobilization of high‐level nuclear waste with compositions (SiO2 )0.477 (B2 O3 )0.239 (Na2 O)0.170 (TiO2 )0.023 (CaO)0.068 (Al2 O3 )0.023 and (SiO2 )0.482 (B2 O3 )0.244 (Na2 O)0.220 (BaO)0.054 were subjected leaching experiments under hydrothermal conditions in an autoclave at 200°C for different time durations. Morphological and structural transformations associated with leaching, have been monitored with techniques like XRD, SEM, solid‐state nuclear magnetic resonance. XRD and SEM along with NMR studies have confirmed that, upon leaching, formation of an aluminosilicate phase, Zeolite‐P (Na6 Al6 Si10 O32 ·12H2 O), occurs with NBS glass. BBS glass upon subjecting to the same conditions leads to formation of multiple amorphous phases having Q 4 (silica rich phase) and Q 3 structural units of Silicon along with structurally modified residual glass. Upon leaching BO3 structural units preferentially get released from BBS glass. Comparison of results with international simple glass confirmed that, for the latter, mass loss rates are one order of magnitude lower.